Workplace Spirituality, Religiosity and Employee Performance: A Study of Service Sector Organization in Saudi Arabia - Alkhathran, Ohoud Yousef Saad (2011)
Tremendous research has noticed the impossibility of disentangling human with their spirituality and their religiosity. Many researchers have long echoed the importance of spirituality and religiosity in recent modern organizations. Thus both cannot be disentangled of from employee personalities and performance at the workplace and these two can be of distinct interest as people's culture and ideology differ. Thus this study is aimed at exploring the relationship between workplace spirituality and Islamic religiosity with employee performance in the Riyadh Bank of Saudi Arabia. This study investigates 142 staff from three different branches of Riyadh Bank (Riyadh, Jeddah, and Dammam). The result of the correlation, and multiple regressions revealed that workplace spirituality and Islamic religiosity positively affect employee performance. Conclusively all the hypotheses of this study are tested correctly and the research question are well answered. This research ends by recommending to future research explore the effect of other religious content on employee performance in cooperate organizations.